Structural and Morphological Characterization of Sr0.6Ba0.4Ce0.9Ga0.1O3-Δ for Proton-Conducting Solid Oxide Fuel Cell Application - Wardah Norman, Nur; Nor Anasuhah Wan Yusoff, Wan; Abdul Samat, Abdullah; Rao Somalu, Mahendra; Muchtar, Andanastuti (International Journal of Engineering and Technology, 2019)
Sr0.6Ba0.4Ce0.9Ga0.1O3-δ (SBCG) electrolyte pellet was prepared by glycine-nitrate method, in which the electrolyte powders and pellets were systematically characterized for their application to proton-conducting solid oxide fuel cells (SOFCs). Thermogravimetric analysis revealed that impurities were formed in the electrolyte powders at the temperature of 1000 °C. X-ray diffraction analysis showed that the powder calcined at 1000 °C produced an electrolyte with high purity. Scanning electron microscopy analysis indicated that the sintered SBCG pellet had a clear morphology and grain boundaries. Therefore, SBCG is a promising electrolyte for SOFC applications.